Comparação entre enxerto ósseo autógeno e rhMP-2 (infuse Bone Graft) na reconstrução de maxila atrófica anterior - Freitas, Rubens Moreno de [UNESP] (2013)
The objective of this study was to compare bone augmentation in the anterior maxilla following implantation of rhBMP2/ACS vs. autogenous bone graft. In this study, 24 patients were selected and equally randomized into 2 groups: Group 1 - rhBMP2/ACS or Group 2 - intraoral particulated autogenous bone graft. A titanium mesh was used for space provision in both Groups. Average clinical bone gain, histological/histomorphometrical (core biopsy obtained at 6 month), CBCT (preoperative, 3 and 6 months follow-up) and real time PCR (new bone scraped at 6 months) were used as evaluation methods. Clinical healing was generally uneventful. Mean clinical ridge width increased 3.2±0.9 vs. 3.7±2.1 mm (p=0.31) for Group 1 and Group 2, respectively. Group 1 yielded statistically significant CBCT bone gain only at subcrestal level compared with Group 2 (1.5±0.7 vs. 0.5±0.9mm; p=0.01). In the histological analysis, specimens from group 1 showed bone marrow significant richer in cells and capillaries (p=0.002) than Group 2, however no difference was found in other parameters. Real time PCR showed higher expression of genes BMP2 and Runx2 in Group 1 (p=0,001 e p=0,0021, respectively) and RANKL:OPG, BSP and OPN in Group 2 (p=0,01, p=0,005 and p=0,0009, respectively). A total of 62 implants were installed after 6 months. In conclusion, Group 1 supported clinically and tomographically relevant alveolar ridge augmentation of comparable magnitude to Group 2, presenting more favorable histological and gene expression results, suggesting an alternative for autogenous bone graft.